2006
DOI: 10.2514/1.16577
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Multidisciplinary Optimization Techniques Applied to a Reusable Launch Vehicle

Abstract: Three multilevel multidisciplinary optimization techniques, Bi-Level Integrated System Synthesis, Collaborative Optimization, and Modified Collaborative Optimization, are applied to the design of a reusable launch vehicle, evaluated, and compared in this study. In addition to comparing the techniques against each other, they are also compared with designs reached via fixed-point iteration of disciplines with local optimization and the industry accepted multidisciplinary optimization technique, All-at-Once. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 8 publications
1
48
0
Order By: Relevance
“…However, the results of Brown and Olds [143] show strange behavior in a practical design problem. In particular, when the penalty parameter was above a threshold value, the algorithm could not improve on the initial design point.…”
Section: Collaborative Optimization (Co)mentioning
confidence: 93%
See 1 more Smart Citation
“…However, the results of Brown and Olds [143] show strange behavior in a practical design problem. In particular, when the penalty parameter was above a threshold value, the algorithm could not improve on the initial design point.…”
Section: Collaborative Optimization (Co)mentioning
confidence: 93%
“…These problems can be mitigated by the use of surrogate models or reduced-order modeling as described above. The one benchmarking result available for BLISS-2000 is the launch-vehicle design problem of Brown and Olds [143]. In this case, BLISS-2000 tended to outperform other distributed architectures, and it should be cost-competitive with other monolithic architectures when coarse-grained parallel processing is fully exploited.…”
Section: E Bilevel Integrated System Synthesis (Bliss)mentioning
confidence: 99%
“…Results from various studies have shown that the performance of a method can be dependent on its implementation, the characteristics of the problem being solved, and the optimizer employed (Alexandrov and Kodiyalam 1998;Brown and Olds 2006;Perez et al 2004). Furthermore, for some problems, specific methods may either fail to return an optimum, or may not be suited to implementation (Brown and Olds 2006). Additionally, comparing results between studies can be difficult as the performance of an MDO method can depend on specific implementation details.…”
Section: Introductionmentioning
confidence: 96%
“…Typically the selection of an MDO method is done in an ad hoc manner, since few benchmarking studies are available to make an informed decision (Alexandrov and Kodiyalam 1998). Results from various studies have shown that the performance of a method can be dependent on its implementation, the characteristics of the problem being solved, and the optimizer employed (Alexandrov and Kodiyalam 1998;Brown and Olds 2006;Perez et al 2004). Furthermore, for some problems, specific methods may either fail to return an optimum, or may not be suited to implementation (Brown and Olds 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The structure is a space module of the International Space Station (ISS) designed by ALCATEL ALENIA Space. An example of the use of a CO approach to the aerospace application is available in Brown [11] (where a more generic optimization on the global design of a space vehicle, with a comparison of three different methods, is reported) and in Wallace [12], where the philosophy of the CO design is applied as well as it was done for this work. The FE model 2 has an high definition degree and was created taking into account (1) the primary structure (no inside structures are presented) and (2) a large set of loads (Fig.…”
Section: Space Modulementioning
confidence: 99%